Genetic Impact of Second Hand Cigarette Smoke - Zil- (ziauddin University, 2024)
Second hand smoke is a complex mixture of more than 4000 chemical compounds that are generated during the burning of tobacco products and affects all those who are exposed to smokers in a closed environment either at home or work place. This mixture contains numerous irritants and toxicants which leave severe as well as carcinogenic health effects in humans.